Análise da influência da criatividade e da paixão empreendedora sobre a intenção empreendedora de estudantes universitários - Bignetti, Bernardo (2018)
Entrepreneurship has a great impact on society, creating jobs and fostering regional economic development. In the social and cognitive psychology literature, intentions have been known as a good predictor to a planned behavior, such as the intention to become an entrepreneur. Thus, the Social Cognitive Theory, by Bandura (1986), has been used to expand the understanding on human actions and/ or intentions to act which are influenced by the interaction between cognitive and personal factors and environmental circumstances. Due to the complexity inherent to the study of entrepreneurship and entrepreneurial intentions, other factors and different contexts affecting the antecedents of entrepreneurial intentions are needed to be examined. As such, the impact of entrepreneurial passion and creativity on entrepreneurial intention, in a developing South American country, like Brazil, could be explored. Hence, this work has aimed to analyze the relationship between creativity and entrepreneurial passion on entrepreneurial intention, using the framework of the Social Cognitive Theory. A quantative research method was adopted, conducted through a survey of university students at PUCRS, from two different graduation courses and approaches: i) business management (managerial approach) and ii) computer science (technical approach). In all, 338 valid responses were obtained, which were analyzed through structural equation modeling technique, enabling the validation of the theoretical model proposed and the test of five hypothesis. The results showed both a direct and indirect positive relationship between entrepreneurial passion on entrepreneurial intention. Regarding the creativity factor, results indicated only an indirect effect of creativity on entrepreneurial intention, being this relationship mediated through selfefficacy. In addition, results indicated no significant differences when examined in relation to age, gender, type of course, entrepreneurial family background, role models, risk propensity and family income. However, in relation to the course progress, a possible difference in the relation between creativity and self-efficacy was observed in the model examined. This work contributes, from a practitioner point of view, in underlining the university´s role, through courses and workshops, in increasing the self-efficacy among graduates students, as well as stimulating the individual passion to become an entrepreneur, in order to expand entrepreneurial intention. From a theoretical point of view, this work supports existing literature on the positive impact that creativity and entrepreneurial passion have on entrepreneurial intentions, especially considering the mediator role of self-efficacy. Also, it validates a theoretical model based on the Social Cognitive Theory in a developing South American background, Brazil.